A Regularity‐Based Fullerene Interfacial Layer for Efficient and Stable Perovskite Solar Cells via Blade‐Coating. (1st October 2021) - Li, Jiaxuan; Meng, Xiangchuan; Huang, Zengqi; Dai, Runying; Sheng, Wangping; Gong, Chenxiang; Tan, Licheng; Chen, Yiwang
Abstract: The electron transport layer (ETL) plays a crucial part in extracting electron carriers while optimizing the interfacial contact of perovskite/electrode in planar heterojunction perovskite solar cells (PVSCs). Despite various ETLs being designed for efficient PVSCs, there exists hardly any research on the effect of molecular stacking order on device performance. Herein, poly(ethylene‐ co ‐vinyl acetate) (EVA) is employed as the [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PC61 BM) solution additive. The strong binding energy between EVA with PC61 BM promotes the molecular stacking order of ETLs, which alleviates the morphology inhomogeneity, possesses a matched energy level, blocks ion migration, and improves the water–oxygen barrier of perovskite devices. The blade‐coated MAPbI3 ‐based PVSCs achieve a power conversion efficiency (PCE) of 19.32% with positive reproducibility and negligible hysteresis, as well as maintain 90% and 80% of the initial PCE after storage under inert and ambient conditions (52% humidity) for 1500 h without encapsulation. This strategy also improves the champion PCE of CsFAMA‐based PVSCs to 20.33%. These findings demonstrate that the regulation of molecular stacking order is a valid approach to optimize interfacial charge‐carrier recombination in PVSCs, which meet the demand for high‐performance ETL in large‐area PVSCs and improve the upscaling of the fabrication technology toward practical applications. Abstract : The electron transport layer (ETL) plays a crucial part in extracting electrons and optimizing interfacial contact for perovskite solar cells (PVSCs). Herein, the EVA is introduced into PC61 BM to promote the orderly molecular stacking of ETLs. The PC61 BM:EVA‐based MAPbI3 PVSCs deliver a champion efficiency of 19.32% and regain 80% of initial efficiency after storage under 52% humidity for 1500 h.